Passive Removal of Silicone Oil with Temporal Head Position through Two 23-Gauge Cannulas - Zhong Lin; Zhi Sheng Ke; Qian Zheng; Zhen Quan Zhao; Zong Ming Song (Journal of Ophthalmology)
Purpose. To report a new approach for removal of silicone oil. Methods. All surgeries were performed using 23-gauge vitrectomy system with two transconjunctival sutureless cannulas. At the beginning, most of the silicone oil was removed by traditional microinvasive vitrectomy system through inferior-temporal cannula. Then, the blood transfusion tube is removed from the inferior-temporal cannula, and the fluid-air exchange is performed. A passive fluid-air exchange was performed to aspirate the residual silicone oil after gradually turning the patient’s head temporally by approximately 90° gradually. Results. After the surgery, all patients had a clear anterior chamber and vitreous cavity on slit lamp and B scan examination, respectively. The mean time taken for silicone oil removal and total surgery was 8.0±1.4 minutes and 12.4±2.5 minutes, respectively. The mean intraocular pressure 1 day, 3 days, 1 week, 1 month, and 3 months after surgery was 9.0±5.8 mmHg, 11.3±7.6 mmHg, 16.1±6.9 mmHg, 17.7±4.8 mmHg, and 17.1±3.5 mmHg, respectively. Conclusion. This new approach may provide a safe and fast method to remove the silicone oil.